Islamic Religious Education Teacher Learning Methods During the Covid-19 Pandemic Period in Junior High Schools - Anggun Mursyida; Rini Rahman; Fadila Yulianti; Muhammad Taufan (International Journal of Multidisciplinary Research of Higher Education, 2022)
The Islamic Religious Education learning method is an important component of learning. In providing learning materials the teacher must have preparation so the teacher must know the appropriate learning methods to apply when teaching. The purpose of this study was to find out what learning methods were applied at Sijunjung 19 Public Junior High School during the Covid-19 pandemic. This study used a qualitative method with a case study approach, data sources were taken from sixteen informants consisting of teachers and students through direct interviews using a set of interview protocols. All data were analyzed thematically using NVivo 12 software. The research findings show that there are three Islamic Religious Education learning methods that are often applied by teachers, namely: i) Lecture method, ii) recitation, and iii) group discussion.